Impact of thyroid dysfunction on short-term outcomes and long-term mortality in patients with pulmonary embolism. Issue 211 (March 2022) - Pohl, Kristina R.; Hobohm, Lukas; Krieg, Valentin J.; Sentler, Carmen; Rogge, Nina I.J.; Steimke, Laura; Ebner, Matthias; Lerchbaumer, Markus; Hasenfuß, Gerd; Konstantinides, Stavros; Lankeit, Mareike; Keller, Karsten
Abstract: Background: A large body of evidence suggest an impact of thyroid function on outcomes of cardiovascular diseases, but results for acute pulmonary embolism (PE) are sparse. Methods: We analysed the impact of hypothyroidism as well as hyperthyroidism on the short and long-term outcomes of patients with acute PE. The impact was compared to the group of euthyroid PE patients as reference group. Results: Overall, 831 PE patients (median age 69 [IQR 56–77] years; 52.2% females) were analysed. Among these, 734 patients (88.3%) were classified as euthyroid, 40 (4.8%) as hypothyroid and 57 (6.9%) as hyperthyroid. PE patients with hypothyroidism had higher rates of adverse in-hospital outcomes (37.5% vs. 11.6%, P  < 0.001), PE-related (22.5% vs. 4.8%, P < 0.001) and all-cause in-hospital death (25.0% vs. 6.8%, P < 0.001), whereas hyperthyroidism did not affect in-hospital outcomes. Long-term mortality was higher in hypothyroidism (52.5% vs. 28.9%, P  = 0.002) and hyperthyroidism (43.9% vs. 28.9%, P  = 0.018) compared to euthyroid function. In the 750 normotensive PE patients, hyperthyroidism affected adverse in-hospital outcome (OR 2.58 [95%CI 1.12–5.97], P  = 0.026) and PE-related in-hospital mortality (OR 3.50 [95%CI 1.10–11.17], P  = 0.035) in comparison to euthyroid PE patients, while hypothyroidism showed no influence. Elevated fT4 (HR 1.75 [95%CI 1.16–2.63], P  = 0.007) and reduced fT3 values (HR 2.51 [95%CI 1.48–4.28], P  = 0.001) were associated with increased long-term mortality. Conclusion: Thyroid dysfunction had a substantial impact on short and long-term outcomes of patients with acute PE. Elevated fT4 and reduced fT3 values were significantly associated with increased long-term mortality in normotensive PE patients. Highlights: Thyroid dysfunction had a substantial impact on short and long-term outcomes of patients with PE. Hyperthyroidism affected adverse in-hospital outcome in normotensive PE patients. Hypothyroidism showed no influence on in-hospital outcomes in normotensive PE. Elevated fT4 and reduced fT3 were associated with increased long-term mortality in normotensive PE.